2019
DOI: 10.3390/nu11112740
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Independent of Fast Food Are Associated with Obesity among Korean Adults: Korea National Health and Nutrition Examination Survey 2010–2014

Abstract: Few studies have examined the multifaceted aspects of fast food consumption and dietary patterns for their effects on obesity. We examined the independent associations of obesity with fast food consumption and dietary pattern in Korean adults using a nationally representative cross-sectional survey. A total of 19,017 adults aged 19–64 years participated in the Korea National Health and Nutrition Examination Survey (KNHANES) 2010–2014. Fast food items were removed from diet and then dietary patterns were genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Although intake of the FFS pattern in this study does not increase carbohydrate intake, the risk of metabolic syndrome could be increased as it is related to increased fat intake and associated with increased risk of insulin resistance. Also, one other study said that even though fast food is known to be unhealthy, unhealthy dietary patterns including fast food have a stronger correlation with metabolic disorders than fast food consumption on its own [ 33 ]. Therefore, we should carefully consider whether eating the FFS pattern might contribute to metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although intake of the FFS pattern in this study does not increase carbohydrate intake, the risk of metabolic syndrome could be increased as it is related to increased fat intake and associated with increased risk of insulin resistance. Also, one other study said that even though fast food is known to be unhealthy, unhealthy dietary patterns including fast food have a stronger correlation with metabolic disorders than fast food consumption on its own [ 33 ]. Therefore, we should carefully consider whether eating the FFS pattern might contribute to metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…No communication process with the researchers of the studies was required for verification or clarification of the data because data presented in the manuscripts were considered adequate. From these studies, nine were conducted in Asia (People’s Republic of China (Shi et al, 2008, 2011), Korea (Cho et al, 2011; Kim et al, 2012, 2019), Singapore (Whitton et al, 2018), Iran (Hosseini-Esfahani et al, 2012), Lebanon (Matta et al, 2016), India (Satija et al, 2015)), five in the USA (Boggs et al, 2011; Gadgil et al, 2015; Newby et al, 2003, 2004; Schulze et al, 2006), five in South America (Brazil (Cunha et al, 2010; Machado Arruda et al, 2016; Silveira, et al, 2018), Mexico (Denova-Gutiérrez et al, 2011; Flores et al, 2010)), four in Oceania (Australia (Arabshahi et al, 2016; Livingstone and McNaughton, 2017, 2018), New Zealand (Schrijvers et al, 2016)) and three in Europe (Denmark (Togo et al, 2004), Germany (Schulz et al, 2005), Greece (Karfopoulou et al, 2017)). Nine of the studies were prospective (Arabshahi et al, 2016; Boggs et al, 2011; Hosseini-Esfahani et al, 2012; Newby et al, 2003, 2004; Schulz et al, 2005; Schulze et al, 2006; Shi et al, 2011; Togo et al, 2004) and the rest of them had a cross-sectional design (Cho et al, 2011; Cunha et al, 2010; Denova-Gutiérrez et al, 2011; Flores et al, 2010; Gadgil et al, 2015; Karfopoulou et al, 2017; Kim et al, 2012, 2019; Livingstone and McNaughton, 2017, 2018; Machado Arruda et al, 2016;…”
Section: Resultsmentioning
confidence: 99%
“…Each study involved from 123 to 24,958 adult men and/or women with normal body weight, overweight or obesity. Participants’ dietary intake was assessed using 24-hour dietary recalls in six studies (Karfopoulou et al, 2017; Kim et al, 2012, 2019; Livingstone and McNaughton, 2017, 2018; Silveira, et al, 2018), and 7-days dietary records in two studies (Newby et al, 2003, 2004), whereas validated food frequency questionnaires were used in the remaining studies.…”
Section: Resultsmentioning
confidence: 99%
“…First, there may be other dominant factors that have significant effects on the development of NCDs [ 44 ]. This study did not adjust for gender, age, and diet, which have shown effects on NCDs in several studies that used larger datasets [ 45 , 46 , 47 , 48 , 49 ]. Nevertheless, some studies included the factors in the analyses with relatively smaller datasets [ 50 , 51 , 52 ].…”
Section: Limitations and Future Researchmentioning
confidence: 99%